MULTIMEDIA TECHNOLOGIES AS TOOLS FOR FOSTERING DIGITAL LITERACY IN EDUCATION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
This study explores the integration of multimedia technologies into the educational landscape of physical education in Ukraine, considering various forms of education such as face-to-face, mixed, and distance learning, especially under martial law. The purpose of the study is to reveal the attitude of physical education teachers towards the use of MT during physical education, to determine the level of digital literacy of physical education specialists and to outline the ways to improve it. Methodology involves analysis and synthesis of literary sources, surveys conducted among physical education teachers using Google Forms, mathematical data processing, and a pedagogical experiment. Survey results underscore the necessity of integrating multimedia technologies into physical education, with most teachers acknowledging their positive impact on teaching quality but expressing a need for enhanced digital skills. The observed digital literacy level aligns with the basic standard, prompting the development of a program utilizing multimedia technologies to shape the digital literacy of physical education teachers. Digital literacy evaluation employs the Digital Competence Framework for Citizens rooted in UNESCO documents, categorizing competence levels as basic, independent, and professional. The resultant program for nurturing digital literacy among physical education teachers comprises theoretical-organizational, operational, methodical, and assessment components. Experimental testing confirms the program’s efficacy, revealing an improvement in digital literacy from basic to independent user levels and, in some cases, professional competence. In conclusion, this research highlights the positive impact of the program on enhancing the knowledge, skills, and professional aptitude of physical education teachers, poised to improve the effectiveness of physical education in Ukraine and address contemporary educational challenges. Furthermore, the program serves as a foundational framework for advancing multimedia support in the field.